ВПЛИВ РЕОЛОГІЧНИХ ВЛАСТИВОСТЕЙ ДИСПЕРСНОЇ СИСТЕМИ НА ПОКАЗНИКИ ПОЛІРУВАННЯ ПІДКЛАДОК ІЗ СИТАЛУ - Філатов, Юрій; Сідорко, Володимир; Сохань, Сергій; Ковальов, Сергій; Панова, Анна; Ковальов, Віктор; Гаращенко, Віктор; Вєтров, Анатолій (Институт сверхтвердых материалов им. В. Н. Бакуля Национальной академии наук Украины, 2019)
The purpose of this study is to study the laws of the influence of the rheological properties of the dispersed system on the parameters of the polishing process of the sitall substrates. On the basis of the cluster model of removal of the treated material during polishing and the Derjaguin–Landau–Verwey–Overbeek theory, it is shown that the average value of the interaction potential of the grains of the polishing powder with the treated surface and the concentration of the slurry particles in the contact area of the grain of the polishing powder with the treated surface, taking into account their distribution for the surface depends essentially on the thickness of the gap between the elemental sections of the contact surfaces of the workpiece and the tool, which is determined depending on the mode of polishing (the nominal pressure of pressing the workpiece to the tool and relative speed of their movement), the coefficients of surface tension and the dynamic viscosity of the dispersed system, the angles of wetting by a dispersed system, respectively, surfaces of the workpiece and tool. It has been established that the rheological characteristics of the polishing dispersion system do not significantly influence the intensity of removal of the treated material from the surface during polishing and have a slight effect on the roughness of the processed surface. When polishing the substrates from the sitall ST-50-1, high productivity of removing the treated material is achieved and the low roughness of the treated surface, which satisfies the requirements for the sitall substrates.